Suomen merikotkat 2005-2006 - Stjernberg, Torsten; Koivusaari, Juhani; Högmander, Jouko; Ollila, Tuomo; Keränen, Seppo; Munsterhjelm, Gustav; Ekblom, Hannu (Linnut-vuosikirja, 2007)
Sammanfattning: Finlands havsörnar 2005-2006.
Keywords: 2005; 2006; merikotka; petolinnut; havainnot; pesintä; havsörn; rovfåglar; observationer; häckning; Suomi; Finland; uhkat; sähköpylväät; Haliaeetus albicilla